The Grouping of Species Saurauia Willd. in West Sumatera Based on Morphometric Analysis and Pollination System - Burlis, Rikinovtian; Syamsuardi, Syamsuardi; Mansyurdin, Mansyurdin (Metamorfosa: Journal of Biological Sciences, 2019)
Saurauia Willd. is a genus of perennial plant or bush which usually found in highland forest or as rheophyte in rocky areas along the river bed. There are 12 species of this genus found in West Sumatera. The purpose of this research is to analyze the grouping of Saurauia species based on morphometric analysis and determine the pollination system based on pollen-ovule (P/O) ratio. The research has been conducted since September 2014 until December 2015 by using the self-collected specimen and Herbarium ANDA specimen. Morphometric analysis was applied to all 12 species which consist of 21 morphological characters and pollen–ovule (P/O) ratio was applied to 10 species. The results of this research are: generally the euclidian distance is ranged 7.35-14.73. The shortest one is S. cerea and S. laxa which d point is 7.35 and the longest one is S. cerea and Saurauia sp. which the d point is 14.73. Saurauia sp. is closely related with S. leprosa and S. bracteosa which are belonged to same sub cluster and having the same character which are glabrous leaf surface, acuminate apex and 5 similar sepals. Pollen-ovule (P/O) ratio determined the pollination system of Saurauia is xenogami.